Sistem Otomatis Exhaust Berdasarkan Kapasitas Asap Dalam Ruangan Berbasis Internet of Things (IoT) - Andi Kurniawan; Toibah Umi Kalsum; Yessi Mardiana (Jurnal Media Infotama, 2025)
Adeeva Hotel Bengkulu City is one of the hotels in Bengkulu City that provides room rental services, such as rooms for meetings, seminars and parties. Currently, Adeeva Hotel has 4 meeting rooms, two of which are smoking rooms. Currently, there is no system in the room that can detect smoke conditions in the room.In this study using library methods, observation, interviews and laboratories, designing a system that can detect smoke levels in a room, where the sensor will read or detect smoke levels in the room, the sensor used in detecting smoke is the MQ2 sensor. While for data processing using ESP8266 with a program on the tool made using Arduino ide and for the Internet of Things (IoT) using Blynk.The system can detect smoke levels in the room, which is carried out by the MQ2 sensor, the detection results will be processed by ESP8266 where if the smoke levels in the room are large (>) from 10 PPM, ESP8266 will send a command to the relay to turn on the exhaust, so that the smoke in the room will be released out. Besides being based on exhaust sensor detection, it can be turned on and off manually via the application by entering manual mode.